2012
DOI: 10.1186/1471-2148-12-91
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary genomics of mycovirus-related dsRNA viruses reveals cross-family horizontal gene transfer and evolution of diverse viral lineages

Abstract: BackgroundDouble-stranded (ds) RNA fungal viruses are typically isometric single-shelled particles that are classified into three families, Totiviridae, Partitiviridae and Chrysoviridae, the members of which possess monopartite, bipartite and quadripartite genomes, respectively. Recent findings revealed that mycovirus-related dsRNA viruses are more diverse than previously recognized. Although an increasing number of viral complete genomic sequences have become available, the evolution of these diverse dsRNA vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
81
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 100 publications
(83 citation statements)
references
References 48 publications
2
81
0
Order By: Relevance
“…At present, mycoviruses with RNA genomes are classified into 12 families, of which 4 contain dsRNA viruses, 6 comprise (+)ssRNA viruses, and 2 families (Metaviridae and Pseudoviridae) accommodate RNA reverse-transcribing genomes (1). However, an increasing number of mycoviruses that differ from those classified have been found (7)(8)(9). Recently, Kondo et al (10) identified L protein-like gene sequences of a putative (−)ssRNA virus in the genome of Erysiphe pisi, a fungal plant pathogen, and they also assembled incomplete genomic sequences of (−)ssRNA viruses in transcriptome shotgun assembly libraries of another fungal pathogen, Sclerotinia homoeocarpa, and suggested that (−)ssRNA viruses are most likely to exist in fungi (10).…”
mentioning
confidence: 99%
“…At present, mycoviruses with RNA genomes are classified into 12 families, of which 4 contain dsRNA viruses, 6 comprise (+)ssRNA viruses, and 2 families (Metaviridae and Pseudoviridae) accommodate RNA reverse-transcribing genomes (1). However, an increasing number of mycoviruses that differ from those classified have been found (7)(8)(9). Recently, Kondo et al (10) identified L protein-like gene sequences of a putative (−)ssRNA virus in the genome of Erysiphe pisi, a fungal plant pathogen, and they also assembled incomplete genomic sequences of (−)ssRNA viruses in transcriptome shotgun assembly libraries of another fungal pathogen, Sclerotinia homoeocarpa, and suggested that (−)ssRNA viruses are most likely to exist in fungi (10).…”
mentioning
confidence: 99%
“…As more partitiviruses were isolated and their genomes were sequenced, it became clear that some fungal partitiviruses are phylogenetically more closely related to plant partitiviruses than to some other fungal partitiviruses (18,19); therefore, the host-based taxonomic classification of partitiviruses is no longer suitable. To address this inconsistency, the classification of genera in this family has recently been reevaluated (20)(21)(22). A proposal to have the family Partitiviridae be reorganized to include four new genera, Alphapartitivirus, Betapartitivirus, Gammapartitivirus, and Deltapartitivirus, was recently approved by the International Committee for Taxonomy of Viruses (http://talk.ictvonline.org/files/proposals/taxonomy_proposals _fungal1/m/fung04/4772.aspx).…”
mentioning
confidence: 99%
“…The events of horizontal gene transfer (HGT) commonly occur not only between distinct evolutionary lineages of ssRNA, dsRNA, or DNA viruses but also between DNA and ssRNA viruses (7,54,55,56,57,58,59,60). These HGT events have been a major contributor of evolutionary innovation and a driver of speciation and environmental adaptation for viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Mycoviruses with dsRNA genomes are usually encapsidated in rigid particles and are so far classified into six families, including two newly established families, Megabirnaviridae and Quadriviridae (1,5,6). However, an increasing number of newly discovered and characterized dsRNA mycoviruses remain unassigned (7,8).…”
Section: Importancementioning
confidence: 99%